Analyzing the effects of sewing machine needle coating materials on the Needle's heating during sewing - (:unkn) unknown (Ege Universitesi, 2014)
Sewing is the last step of a lengthy mass production process. Garments that break down at this stage due to bad stitching cause a great loss of time, energy and also material. The most important sewing faults are thermal and mechanical faults caused by the sewing needle. During sewing, the fabric resists the penetration of the needle. This frictional resistance between the needle and the fabric produces heat and it causes the needle to overheat during high-speed sewing. Sewing needles coated with three different materials are used in this study. The coating materials of the needles used here are Cr (Chrome), PTFE(Polytetrafluoroethylene) and TiN(Titanium nitride). 50 sewing processes for each kind of coating have been carried out in the study, for a total of 150. Needle temperatures during the sewing process have been measured with an optical pyrometer. According to the findings obtained at the end of the measurements, it's been established that materials used in the needle coating directly affect needle heating. The needles coated with TiN according to data obtained by other needles has been found that less heat.
Keywords: Needle coating; Needle heating; Pyrometre; Sewing machine needle